Sintesis Dan Karakterisasi Membran Silika (Sio2) Untuk Pengolahan Limbah Cair Hotel Pengaruh Variasi Komposisi - Arief Pratama Avisha; Jhon Armedi Pinem; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pollution by domestic waste is not only produced from residential areas nevertheless is also produced by attempt in tourism especially lodging facilities and infrastructure such as hotels. One of the effects is the wastewater that produced by the hotel. The hotel wastewater treatment using membranes by ultrafiltration is an easy and effective way. The fabrication of silica membranes is also assisted by supporting materials that is compound by Polyvynil Alcohol (PVA) and Polyethylene Glicol (PEG). In this researches the synthesis of silica membranes with variations composition of the silica mass 8, 10, and 12 gram. The aim of this researches is to learn the effect of variations composition of the silica mass on the membranes synthesized towards separation of the BOD5, COD, and TSS that contained in hotel wastewater. The deflation level of BOD5, COD, and TSS were done by passing hotel wastewater through the silica membranes which is synthesized. The optimum coefficient of silica membranes rejection for deflation level is BOD5, COD, and TSS repeatedly are 72,12%; 79,09% and 87,61% along the value of flux that produced is 22,562 L/m2.Hour. The getting larger composition of silica membranes, then the measure and tightness of the membranes pore that produced are getting bigger and organized along with the coefficient of rejection (%) will also decrease.Keywords : flux and rejection, hotel wastewater, membrane, silica, ultrafiltration.